An Analysis of Politeness Used in the Red One Movie - Clarissa Cyndi Rose Angelique Tumbol; I Gusti Ayu Agung Sintha Satwika (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2026)
Politeness in communication does not always mean being gentle and soft-spoken, but is a social strategy to maintain relationships with interlocutors who feel valued. This research analyses the types of politeness maxims in the movie Red One (2024) based on Leech’s theory (2014). The data source was obtained from the dialogue between characters in the movie, via the Prime Video platform. This study employs a qualitative method using observation and classification methods based on ten types of politeness maxims. The findings reveal that not all politeness maxims, according to Leech (2014), appear in the movie, but only four maxims with a total of 12 data as follows: generosity maxim 8%, tact maxim 42%, approbation maxim 33%, and sympathy maxim 17%. The tact maxim is the most dominant, which shows a strategy where the speaker minimizes the cost to the interlocutor and maximizes the benefit to the interlocutor.